Pellino-1 Regulates the Responses of the Airway to Viral Infection - Marsh, Elizabeth K.; Prestwich, Elizabeth C.; Williams, Lynne; Hart, Amber R.; Muir, Clare F.; Parker, Lisa C.; Jonker, Marnix R.; Heijink, Irene H.; Timens, Wim; Fife, Mark; Hussell, Tracy; Hershenson, Marc B.; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Exposure to respiratory pathogens is a leading cause of exacerbations of airway diseases such as asthma and chronic obstructive pulmonary disease (COPD). Pellino-1 is an E3 ubiquitin ligase known to regulate virally-induced inflammation. We wished to determine the role of Pellino-1 in the host response to respiratory viruses in health and disease. Pellino-1 expression was examined in bronchial sections from patients with GOLD stage 2 COPD and healthy controls. Primary bronchial epithelial cells (PBECs), in which Pellino-1 expression had been knocked down, were extracellularly challenged with the TLR3 agonist poly(I:C). C57BL/6 Peli1-/- mice and wild type littermates were subjected to intranasal infection with clinically-relevant respiratory viruses; rhinovirus (RV1B) and influenza A. We find that Pellino-1 is expressed in the airways of normal subjects and those with COPD, and that Pellino-1 regulates TLR3 signalling and responses to airways viruses. In particular we observed that knockout of Pellino-1 in the murine lung resulted in increased production of proinflammatory cytokines IL-6 and TNFα upon viral infection, accompanied by enhanced recruitment of immune cells to the airways, without any change in viral replication. Pellino-1 therefore regulates inflammatory airway responses without altering replication of respiratory viruses.